Genome-Wide Association Mapping Indicates Quantitative Genetic Control of Spot Blotch Resistance in Bread Wheat and the Favorable Effects of Some Spot Blotch Loci on Grain Yield - Juliana, Philomin; He, Xinyao; Poland, Jesse; Shrestha, Sandesh; Joshi, Arun K.; Huerta-Espino, Julio; Govindan, Velu; Crespo-Herrera, Leonardo Abdiel; Mondal, Suchismita; Kumar, Uttam; Bhati, Pradeep K.; Vishwakarma, Manish; et al. (Frontiers in Plant Science, 2022)
Spot blotch caused by the fungus Bipolaris sorokiniana poses a serious threat to bread wheat production in warm and humid wheat-growing regions of the world. Hence, the major objective of this study was to identify consistent genotyping-by-sequencing (GBS) markers tagging genomic regions associated with spot blotch resistance using genome-wide association mapping on a large set of 6,736 advanced bread wheat breeding lines from the International Maize and Wheat Improvement Center, phenotyped as seven panels at Agua Fria, Mexico between the 2013-2014 and 2019-2020 crop cycles. We have identified 214 significant spot blotch associated GBS markers in seven panels, among which only 96 were significant in more than one panel. The 96 consistent GBS markers were on chromosomes 1A, 1B, 1D, 2A, 3B, 4A, 5B, 5D, 6B, 7A, 7B and 7D, including markers possibly linked to the Sb1, Sb2 and Sb3 genes. Allelic fingerprinting of the consistent spot blotch associated markers indicated that the percentage of favorable alleles in the lines is significantly associated with their spot blotch response, implying quantitative genetic control of resistance. An interesting finding in this study was the association of the spot blotch favorable alleles at the 2NS translocation, and markers 3B_2280114 and 3B_5601689 with grain yield evaluated in multiple environments. Overall, the results presented here have extended our knowledge on the genetic basis of spot blotch resistance in bread wheat and further efforts to improve genetic resistance to the disease are needed for reducing current and future losses under climate change.